2014
DOI: 10.1007/s00464-014-3899-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical workload in the operating room: primary surgeon versus assistant

Abstract: Intra-individual workload differences do not relate to intraoperative role of surgeons when length of surgery is considered as covariate. An intelligent operating management that considers the length of surgeries by implementing short breaks could contribute to the optimization of intraoperative workload and the preservation of surgeons' health, respectively. The value of mobile health systems for continuous psychophysiologic workload assessment was shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 39 publications
3
33
1
Order By: Relevance
“…Comparing intraoperative workload across the surgical team, the surgeon reported the highest workload for each questionnaire subscale except mental demand, which was the highest for surgeons in training (residents). The mental and physical demands reported by surgeons were consistent with previously published ranges [ 11 , 22 , 39 , 41 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 88%
“…Comparing intraoperative workload across the surgical team, the surgeon reported the highest workload for each questionnaire subscale except mental demand, which was the highest for surgeons in training (residents). The mental and physical demands reported by surgeons were consistent with previously published ranges [ 11 , 22 , 39 , 41 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 88%
“…Excessive training demands and related lifestyle issues, nurture this poor state of well-being [ 2 , 8 , 9 , 10 , 11 ], which may lead to burnout, a state characterized by emotional exhaustion, depersonalization and lack of personal accomplishment, ultimately associated with serious thoughts of leaving training [ 12 , 13 , 14 , 15 ]. A recent U.S. publication revealed for instance that, of the surgical residents who considered leaving the residency (44%), a majority met the criterion for burnout [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In situations imposing a high cognitive demand, there is a sympathetic predominance, increasing the LF/HF ratio. LF/HF ratio has been used as an objective and real‐time measure of cognitive load.…”
Section: Resultsmentioning
confidence: 99%
“…In general, studies presenting a higher MERSQI score were those that used an RCT design. The main characteristics of all included studies, as well as the MERSQI score for each are shown in Table S2 (supporting information).…”
Section: Resultsmentioning
confidence: 99%